2008
DOI: 10.1073/pnas.0802485105
|View full text |Cite
|
Sign up to set email alerts
|

Cultural route to the emergence of linguistic categories

Abstract: Categories provide a coarse-grained description of the world. A fundamental question is whether categories simply mirror an underlying structure of nature or instead come from the complex interactions of human beings among themselves and with the environment. Here, we address this question by modeling a population of individuals who co-evolve their own system of symbols and meanings by playing elementary language games. The central result is the emergence of a hierarchical category structure made of two distin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
188
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(194 citation statements)
references
References 22 publications
6
188
0
Order By: Relevance
“…To remedy this new approaches, e.g. in the form of human computation [2], can be applied [31], as well as so-called category games [26].…”
Section: Discussionmentioning
confidence: 99%
“…To remedy this new approaches, e.g. in the form of human computation [2], can be applied [31], as well as so-called category games [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that the social distribution of individuals is an important factor in the evolution of languages [13,6,10]. This distribution is modeled in our MAS by the underlying interaction topology.…”
Section: Interaction Topologiesmentioning
confidence: 99%
“…Several studies show that the social structure of a population affects how a language emerges [13,6,10]. This motivates that we further explore how different complex networks, such as small-world [19] and scale-free [1], as underlying topologies of our MAS may influence the adaptation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains to be explained how those new semiotic conventions can be generated in the absence of an a priori common code. Computer simulations, using reinforcement-learning algorithms, have shown that communication systems can arise without the presence of common knowledge (Barr, 2004;Kirby & Hurford, 2002;Puglisi, Baronchelli, & Loreto, 2008;Steels, 2003). For instance, two computer agents can share novel symbols by virtue of guesses and explicit performance feedback (Steels, 2003).…”
Section: Existing Accounts Of Human Communicationmentioning
confidence: 99%